FOREST PEDOLOGY IN UKRAINE - Migunova, O. S.; Tihonenko, D. G. (Forestry and Forest Melioration, 2018)
The study of forest soils of Ukraine began in a period of V. V. Dokuchaev’s expedition in Poltava (1888-1894). Systematic studies of soils in forest plantations were begun by G. M. Vysotsky on Velyko-Anadolsky area of the Special expedition (1892-1904). In 1930, after the creation of Ukrainian RIFFM (Research Institute of Forest & Forest Melioration) the investigations in the field of forest pedology are mostly performed by the staff of this institute. In the years 1955-1975 the Laboratory of Pedology of URIFFM carried out the study of the circulation of substances in the “forest-soil” system (I. I. Smolyaninov). Long-term studying of the dynamics of mobile forms of NPK in the upper soil horizons showed no differences in their regular content in different types of forest on Northern Steppe and Polissya permanent study areas. In 1960-1970, the researches of Laboratory of Forest Pedology and Microbiology of URIFFM were focused on the study of inarable lands (eroded, saline, dumps, sandy arenas, dried and undried bogs) to create forest plantations (O. S Gladkii, O. S. Migunova). It is proved that soil nutrient status is determined by the largest amount of bulk phosphorus and potassium available in root layer (O. S. Migunova). In 1976-2000? the Laboratory was studying the use of organic and mineral fertilizers in forests, forest plantations, nurseries and greenhouses (V. N. Ugarov and others). The vegetation properties of soils of different forest types of Left-bank Forest-Steppe were studying for the last 5 years (S. P. Raspopina). For many years, the grand-scale work on studying of forests and forest soils of south-eastern Ukraine are conducted by the Geobotany Department of Dnipropetrovsk University under the direction of A. L. Belgard and A. P. Travleev. The forests and sandy arenas soils, gullies, flood plains were inspected. In 1962-1967 the workers of Soil Science Department (G. S. Grin, A. O. Georgi, D. G. Tykhonenko) and Botany Department of Kharkiv agrarian institute conducted soil and geobotanical inspection of upland oak forests and forests of the sandy terrace of the Siverskiy Donets river. Researches conducted by D. G Tykhonenko, K. B. Novosad, D. V. Gavva showed that forest plantations on arable black earth contribute to the renewal of almost all indexes of their fertility to the level of virgin soil analogues. The prevailing part of scientific activities on forest pedology in Ukraine is conducted on principles of forest typology, the main of which is an understanding of the determinative role of soil fertility and the united study of soils and plantings that grow on them. We name it ecological direction.